Evaluation of ovicidal activity of plant extracts on Tetranychus urticae Koch (Acari: Tetranychidae) - Rodríguez-Cabrera, Miriam; Pérez-Torres, Betzabeth; Aragón-García, Agustín; Ortiz-García, Carlos; Marco Mancebón, Vicente; López-Olguín, Jesús (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The ovicidal activity of ethanol and hexane extracts of Azadirachta indica A. Juss., Trichilia havanensis Jacq., Roldana ehrenbergiana (Klatt) H. Rob. & Brettell, Argemone mexicana L., Schinus molle L. y Gliricidia sepium (Jacq.) Kunth ex Walp. was evaluated in the laboratory on Tetranychus urticae Koch (Acari: Tetranychidae). The extracts (treatments) were applied by spraying at a concentration of 1,000 mg.L-1 to a known number of eggs (age <18h) on leaf discs of bean (Phaseolus vulgaris L.) (10 leaf discs per treatment), and the percentage of egg mortality was recorded after six days of the treatment. The corrected mortality (percentage) was obtained for each test unit, and a simple ANOVA, followed by multiple comparison of means by the Tukey method (α=0.05), were used to find statistically significant differences between treatment effects. The ethanol and hexane extracts of T. havanensis seeds caused an average corrected egg mortality of 77.7±3.5 and 58.0±3.4 %, respectively, which was significantly higher than the egg mortality caused by the other extracts. The ethanol extracts of the other plant species caused a corrected egg mortality, which ranged from 8.8±9.6 to 42.9±8.3 %, while the corrected mortality of the hexane extracts ranged from 0.2±2.3 to 30.1±4.0 %. The results show that the ethanol extract of T. havanensis seeds has good potential for the development of products with biological activity for the management of T. urticae.